Quantum properties of the three-mode squeezed operator: triply concurrent parametric amplifiers - El-Orany, Faisal A.A; Messikh Azeddine, Azeddine; Mahmoud Ahmed, Gharib Subhi; Wahiddin, Mohamed Ridza (Elsevier, 2010)
In this paper, we study the quantum properties of the three-mode squeezed operator. This operator is constructed from the optical parametric oscillator based on the three concurrent χ(2) nonlinearities. We give a complete treatment for this operator including the symmetric and asymmetric nonlinearity cases. The action of the operator on the number and coherent states is studied in the framework of squeezing, secondorder correlation function, Cauchy–Schwartz inequality and single-mode quasiprobability function. The nonclassical effects are remarkable in all these quantities. We show that the nonclassical effects generated by the asymmetric case–for certain values of the system parameters–are greater than those of the symmetric one. This reflects the important role for the asymmetry in the system. Moreover, the system can generate particular types of the superposition states.